HIV Infection Indicator Disease-Based Active Case Finding in a University Hospital: Results from the SHOT Project - Andrea De Vito; Agnese Colpani; Maria Sabrina Mameli; Paola Bagella; Vito Fiore; Claudio Fozza; Maria Antonia Montesu; Alessandro Giuseppe Fois; Fabiana Filigheddu; Noemi Manzoni; Carlo Putzu; Sergio Babudieri; et al. (MDPI AG, 2023)
In 2014, UNAIDS launched renewed global targets for HIV control to achieve by 2025, known as "the three 95": 95% of people living with HIV (PWH) diagnosed, of which 95% are receiving treatment, of which 95% are on sustained virological suppression. In Italy, new HIV diagnoses have been steadily decreasing since 2012. However, in 2020, 41% of new diagnoses presented with less than 200 CD4+ cells/µL and 60% with less than 350 CD4+ cells/µL. Implementing testing and early treatment is a key strategy to prevent AIDS, late presentation, and HIV transmission. We selected non-Infectious Diseases Units based on the European project HIDES and engaged colleagues in a condition-guided HIV screening strategy. We enrolled 300 patients, of which 202 were males (67.3%) and 98 were females (32.7%). Most of the screening was performed in Infectious Diseases (ID) and Hematologic wards. In total, we diagnosed eleven new HIV infections with a hospital prevalence in the study population of 3.7%. Five (45.4%) had a CD4 count <100/mm3, one (9.1%) <200/mm3, and one (9.1%) <300/mm3. Regarding risk factors, 81.8% declared having had unprotected sexual intercourse and 54.5% were heterosexual. All patients promptly started a combination antiretroviral regimen and 10 (90.9%) obtained an undetectable HIV-RNA status. Eight of the eleven (72.7%) patients are currently on follow-up in our outpatient clinic. A proactive indicator disease-guided screening can help avoid missed opportunities to diagnose HIV infection in a hospital setting. Implementing this kind of intervention could favor early diagnosis and access to treatment.